The Utility of Apparent Diffusion Coefficient Values in the Risk Stratification of Prostate Cancer Using a 1.5 T Magnetic Resonance Imaging Without Endorectal Coil - Lopes Dias, J (2016)
Purpose: To evaluate the relationship between mean apparent diffusion coefficient (ADC) and post-surgical Gleason scores. To determine the diagnostic accuracy of multiparametric magnetic resonance imaging (mp-MRI) on a 1.5 T magnet in distinguishing low, intermediate and highgrade prostate tumors. Material and methods: This is a retrospective institutional-review-board-approved, singlecenter study including 30 patients (median age, 60 years) who underwent mp-MRI before prostatectomy for prostate cancer. Using histological reports for guidance, the tumors were localized in ADC maps, and mean ADCs were measured and examined for correlation with Gleason scores. 2 patients had 2 measurable foci, so a total of 32 tumors were studied. The diagnostic accuracy of the mean ADC was assessed by using the area under the receiver operating characteristic curve (ROC). Results: In the differentiation of tumors with a Gleason score of 6 from those with a Gleason score of at least 7, mean ADC yielded an AUC of 0.76 (95% confidence interval: 0.59, 0.93). In the differentiation of tumors with Gleason scores of 6 or 7 from those with a Gleason score of at least 8, mean ADC yielded an AUC of 0.94 (95% confidence interval: 0.86, 1.00). Conclusion: Mean ADC values may allow a correct assessment of the patient risk using a 1.5 T magnet without ERC.